2017
DOI: 10.3389/fphys.2016.00662
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum: Inflammatory Cytokines and BDNF Response to High-Intensity Intermittent Exercise: Effect the Exercise Volume

Abstract: In the "Abstract" Section, there was a mistake in the BDNF-values of the HIIE1.25, once the values of the standard deviation were spliced and did not contain the comma. HIIE1.25: 9.71 ± 306 is incorrect, the correct value is HIIE1.25: 9.71 ± 3.06.In the last sentence of the "Abstract", the word "duration" was misspelled as "durantion".In the "Results" Section, the last word of the first paragraph there is an error in spelling the word duration, appears as duation.Finally, in the "Discussion" Section, the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although it would have been logical to initiate this muscle-brain crosstalk section with a paragraph dedicated to cytokines, the evidence of a direct impact of these molecules on cerebral BDNF production remains inconclusive despite it has been demonstrated that IL-6 can cross the BBB (Banks et al, 1994). The same lack of direct evidence exists for IL-10 or TNF-α even though studies have reported a similar pattern of variation with BDNF in the hippocampus (Noga et al, 2007;Cabral-Santos et al, 2016;Jahangiri et al, 2019). In contrast, several myokines have been identified, bolstered by compelling scientific rationale, establishing a causative link to brain BDNF expression.…”
Section: Muscle-brain Crosstalkmentioning
confidence: 99%
“…Although it would have been logical to initiate this muscle-brain crosstalk section with a paragraph dedicated to cytokines, the evidence of a direct impact of these molecules on cerebral BDNF production remains inconclusive despite it has been demonstrated that IL-6 can cross the BBB (Banks et al, 1994). The same lack of direct evidence exists for IL-10 or TNF-α even though studies have reported a similar pattern of variation with BDNF in the hippocampus (Noga et al, 2007;Cabral-Santos et al, 2016;Jahangiri et al, 2019). In contrast, several myokines have been identified, bolstered by compelling scientific rationale, establishing a causative link to brain BDNF expression.…”
Section: Muscle-brain Crosstalkmentioning
confidence: 99%
“…27 The effect of physical activity on fatigue happens mainly through interplay of BDNF and pro-inflammatory cytokines. 3,4,14,28 However, there are controversial findings about serum BDNF concentration after certain exercise program. For example, studies have reported no changes in exercise-induced serum BDNF levels in MS individuals following moderate aerobic training program.…”
Section: Discussionmentioning
confidence: 99%
“…These results have increased the interest to investigate the potential effects of circulatory BDNF induced by continuous exercise in MS and the fate of locally produced BDNF in CNS tissue as well. 14,15,22,23 On the one hand, BDNF-gene is a stress sensitive gene that responds to glucocorticoid hormones, secreted during stress reactions like in exercise. That interplay is mechanism that shows important effect on disease because it is well known that small amounts of glucocorticoids support normal brain function, and the opposite, stimulation excess by these hormones causes stress-related affective disorders.…”
Section: Introductionmentioning
confidence: 99%